Re-visioning the Future of Education for Native Youth in Rural Schools and Communities - Susan C. Flaircloth (Journal of Research in Rural Education, 2009)
In Learning to Leave, Corbett (2007) argues that (1) education has served as a tool to disassociate students" both physically and culturally"from the places from which they come, particularly if they are from rural places, in effect creating an ambivalence toward education; (2) the ways in which individuals express this ambivalence is shaped, in large part, by factors such as socioeconomic status and gender, and I would argue race and ethnicity; (3) the purpose of schooling is often in conflict with the values and beliefs of rural communities (i.e., formal education may run counter to local forms of social or cultural capital, and it may also be locally perceived as having little effect on the ability of students to increase their economic capital within the rural context); and (4) the effects of globalization are found in many rural areas as evidenced by increasing access to services typically found in more urban areas; thereby decreasing individuals' need to migrate out of these areas.